The Evaluation of Glypican-3 mRNA and Alpha-fetoprotein mRNA as biomarker for hepatocellular carcinoma in Dogs: A preliminary study - Phosri, Aphinan; Pringproa, Kidsadagon; Thitaram, Niyada; Chantawong, Pinkarn; Chuammitri, Phongsakorn; =Thongtharb, Atigan (Veterinary Integrative Sciences (Online), 2025)
Glypican-3 (GPC-3) and alpha-fetoprotein (AFP) are considered powerful biomarkers for human hepatocellular carcinoma (HCC). The elevation of GPC-3 and AFP gene expression is commonly found in individual HCC patients. The detection of these biomarkers can be achieved with the examination of blood or tissue samples. Moreover, mRNA expressing GPC-3 and AFP are evaluated for detecting HCC in patients. In veterinary practice, data on GPC-3 and AFP of gene expression remain limited. Therefore, this study aims to evaluate the GPC-3 and AFP gene expression in dogs with HCC compared with other hepatic diseases. Twenty dogs were divided into two groups: HCC (n=6), and non-HCC (n=6). The liver tissue and plasma samples of each group were examined for GPC-3 and AFP gene expression by qPCR. The results showed a no statistical difference in the expression levels of GPC-3 gene in liver and plasma samples of dogs with HCC compared with non-HCC dogs. However, there was a positive correlation between the expression of GPC-3 gene and levels of aspartate transaminase (AST) in the HCC group (p-value = 0.002, R = 0.967). Moreover, the sensitivity, specificity, and accuracy of GPC-3 gene expression were higher than AFP gene expression in the HCC group. Therefore, this study conveys the expression of GPC-3 gene and AFP gene, suggesting a potential association with the development of HCC in dogs. The findings, particularly regarding the GPC-3 gene, could contribute to improved diagnostic methods in the future.